LAMINAR NATURAL CONVECTION HEAT TRANSFER BETWEEN DUCTED PARALLEL PLATES (Journal of Engineering, 2008)
Laminar natural convection heat transfer to air flow in a ducted two parallel plates subjected to same constant heat flux has been studied experimentally. In this study a test rig has been designed and constructed to allow studying the effect of plate spacing and plates angle of inclination on the heat transfer process. The study covers three plate spacing 15 mm, 35mm and 60 mm that makes plate aspect ratio (AR) 24, 10.285 and 6, The heat flux implemented in all test runs varies between 55 W/m2– 340 W/m2 that makes the modified Rayleigh number (Ra) varies from 105-108. Experimental results presented as plate temperature distribution, variation of local heat transfer coefficient and the relation between Nu and Ra, reveal for the range of parameters mentioned above, an improvement in heat transfer process as the AR values change from 6 to 24 and the improvement rates is higher for the lower heat flux test (lower Ra). A correlation of the results were made in the form of Nuvr (Gr/AR) in which the effect of duct aspect ratio (AR) has been introduced.